"It's one of the few things that … pulls us together when the outside world is really tough." Exploring the outcomes and challenges of a charity-led community garden in a disadvantaged English city. Issue 2 (1st February 2021) - Ramsden, Sam
ABSTRACT: This article explores a charity-led community gardening project working in a disadvantaged community in northern England and provides a detailed analysis of the outcomes for vulnerable people. This article contributes to the research on community gardens by emphasising the need to plan for long-term sustainability. The project received external funding for 3 years and implemented urban agriculture activities based around a community garden and a team of volunteers. The project successfully engaged marginalised people, who strongly voiced outcomes including increased skills and confidence, reduced isolation, improved health and wellbeing, and the opportunity to give back to their local community. Support from staff, volunteering in a team, enjoying gardening and accessing nature provided a strong platform for engagement and impacts. However, there were also significant challenges which required ongoing professional management such as ensuring a safe and comfortable environment. In addition, after the funding finished, the future of the community garden was fragile and marginalised participants were vulnerable to outcomes not being sustained in the long term.